Glycoform-resolved pharmacokinetic studies in a rat model employing glycoengineered variants of a therapeutic monoclonal antibody. Issue 1 (1st January 2021) - Falck, David; Thomann, Marco; Lechmann, Martin; Koeleman, Carolien A. M.; Malik, Sebastian; Jany, Cordula; Wuhrer, Manfred; Reusch, Dietmar
ABSTRACT: Good pharmacokinetic (PK) behavior is a key prerequisite for sufficient efficacy of therapeutic monoclonal antibodies (mAbs). Fc glycosylation is a critical quality attribute (CQA) of mAbs, due to its impact on stability and effector functions. However, the effects of various IgG Fc glycoforms on antibody PK remain unclear. We used a combination of glycoengineering and glycoform-resolved PK measurements by mass spectrometry (MS) to assess glycoform effects on PK. Four differently glycoengineered mAbs, each still containing multiple glycoforms, were separately injected into rats. Rat models have been shown to be predictive of human PK. At different time points, blood was taken, from which the mAbs were purified and analyzed with a liquid chromatography-MS-based bottom-up glycoproteomics approach. This allowed us to follow changes in the glycosylation profiles of each glycoengineered mAb over time. Enzyme-linked immunosorbent assay measurements provided an absolute concentration in the form of a sum value for all glycoforms. Information from both readouts was then combined to calculate PK parameters per glycoform. Thereby, multiple glycoform kinetics were resolved within one mAb preparation. We confirmed increased clearance of high-mannose (Man5) and hybrid-type (Man5G0) glycoforms. Specifically, Man5 showed a 1.8 to 2.6-fold higher clearance than agalactosylated, complex glycans (G0F). Unexpectedly, clearance was even higher (4.7-fold) for the hybrid-type glycan Man5G0. In contrast, clearance of agalactosylated, monoantennary glycoforms (G0F-N) was only slightly increased over G0F (1.2 to 1.4-fold). Thus, monoantennary, hybrid-type and high-mannose glycoforms should be distinguished in CQA assessments. Strikingly, α2, 3-linked sialylation did not affect clearance, contradicting the involvement of the asialoglycoprotein receptor in mAb clearance.